Electoral Reform and Democratic Consolidation in Nigeria: A Comparative Study of the Electoral Act 2022 and Emerging Reform - Yusuf Garba Manjo; Muhammed Olarewaju Yusuf (GREAT : Journal of Global Economic Trends, 2026)
Electoral reform remains a critical component of democratic consolidation in Nigeria due to persistent challenges such as electoral fraud, vote buying, electoral violence, political interference, and declining public confidence in electoral processes. This study examined the role of electoral reform in promoting democratic consolidation in Nigeria through a critical analysis of the Electoral Act 2022 and emerging electoral reform proposals. The study adopted a doctrinal research methodology based on qualitative analysis of primary and secondary sources. Primary sources included the Constitution of the Federal Republic of Nigeria 1999 (as amended), the Electoral Act 2022, judicial decisions, and official policy documents, while secondary sources comprised scholarly literature, election observer reports, institutional publications, and comparative electoral governance studies. The findings reveal that the Electoral Act 2022 introduced important reforms, including the deployment of the Bimodal Voter Accreditation System (BVAS), electronic transmission of results, and enhanced regulatory powers for the Independent National Electoral Commission (INEC), which improved transparency, voter accreditation, and electoral administration. However, the study also found significant legal, institutional, and technological gaps, including implementation ambiguities, infrastructural deficiencies, weak enforcement of electoral offences, and cybersecurity vulnerabilities. Furthermore, emerging reform proposals such as mandatory electronic result transmission, the establishment of an Electoral Offences Commission, strengthening INEC’s independence, and enhanced cybersecurity measures were found to possess significant potential for improving electoral governance. The study concludes that sustainable democratic consolidation in Nigeria requires not only legislative reforms but also strong institutions, reliable infrastructure, effective enforcement mechanisms, and sustained political commitment.